PENCARIAN GAMBAR DI DALAM FOLDER DENGAN INPUT GAMBAR TERPOTONG - Wahyuningrum, Shinta Estri; Leong, Hironimus (PROXIES, 2012)
Habits of computer users are storing data with poor management, this causes the data search process becomes more difficult. Software on a computer that is commonly used for searching process use